Installing Android Studio Apps and the Android SDK: A Quick Guide - rosari J (Agricultural Socio-Economics Journal, 2016)
We learned the fundamentals of Android in the article below. Now we'll talk about how to set up the Android Studio application and the Android Software Development Kit in this article (SDK). Both will be utilised in the development of Android applications.What exactly is Android? Why do developers prefer Android to other platforms?What is the difference between Android Studio and Android SDK?Java is one of the languages that may be used to construct Android apps. Aside from Java, there are various other languages that can be used, including C/C++, Go, and the Kotlin programming language, which Google officially supported in May 2017.